Legal Sanctions Procedure for Electronic Law Enforcement Program Violators in The Jurisdiction of the Malang City Police From A Utilistic Theory Perspective - Sa'adah, Aghniya Ariza (PT. Anagata Sembagi Education, 2026)
The implementation of the ETLE system in Malang City has shown significant results in traffic law enforcement efforts, although it still faces various challenges. The significant gap between the number of detected violations and the number of violators who confirm and pay fines reflects the complexity of the problem. This condition is influenced not only by low public awareness of traffic law compliance but also by the limitations of the ETLE system, which does not allow for the retention of evidence as is the case with manual ticketing.Utilitarianly, ETLE offers many benefits, but its implementation also faces several challenges. Here are some of the main challenges in ETLE application: 1. Implementation Costs. 2. Technical Issues. 3. Data Privacy and Security. 4. Public Acceptance. 5. Regulations ad Policies. Despite its utility, the implementation of ETLE still faces challenges that could diminish its